Anaerobic fermentation featuring wheat bran and rice bran realizes the clean transformation of Chinese cabbage waste into livestock feed - Li, Jiawei; Wang, Cheng; Zhang, Shanshan; Xing, Jinxu; Song, Chunsheng; Meng, Qingwei; Li, Jianping; Jia, Shuo; Shan, Anshan (Frontiers in Microbiology, 2023)
Rapid aerobic decomposition and a high cost/benefit ratio restrain the transformation of Chinese cabbage waste into livestock feed. Herein, anaerobically co-fermenting Chinese cabbage waste with wheat bran and rice bran at different dry matter levels (250, 300, 350 g/kg fresh weight) was employed to achieve the effective and feasible clean transformation of Chinese cabbage waste, and the related microbiological mechanisms were revealed by high-throughput sequencing technology. The bran treatments caused an increase in pH value (4.75–77.25%) and free amino acid content (12.09–152.66%), but a reduction in lactic acid concentration (54.58–77.25%) and coliform bacteria counts (15.91–20.27%). In addition, the wheat bran treatment improved the levels of short-chain fatty acids, nonprotein nitrogen, water-soluble carbohydrates and antioxidant activity and reduced the ammonia nitrogen contents. In contrast, the rice bran treatment decreased the levels of acetic acid, water-soluble carbohydrates, nonprotein nitrogen, ammonia nitrogen, and antioxidant activities. Microbiologically, the bran treatments stimulated Pediococcus, Lactobacillus, Enterobacter, and Weissella but inhibited Lactococcus and Leuconostoc, which were the primary organic acid producers reflected by the redundancy analysis. In addition, Chinese cabbage waste fermented with wheat bran at 350 g/kg fresh weight or with rice bran at 300 g/kg fresh weight increased the scale and complexity of bacteriome, promoted commensalism or mutualism and upregulated the global metabolism pathways, including carbohydrate and amino acid metabolisms. Furthermore, the bran treatments resulted in an increase in bacterial communities that were facultatively anaerobic, biofilm-formed, Gram-negative, potentially pathogenic and stress-tolerant. Collectively, the bran treatments inhibited effluent formation and protein degradation and improved nutrient preservation but reduced organic acid production during the anaerobic fermentation, which is linked to the variations in the bacteriome, indicating that the constructed fermentation system should be further optimized.